PENGARUH KREDIT TERHADAP ARUS KAS PADA PT BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN, TBK. PERIODE TAHUN 2012-2021 - M. Yosep Saeful Anwar M,; Jusuf Nurdin (JEBS (Journal of Economic and Business Student), 2023)
Credit is a form of business undertaken by PT Regional Development Bank of West Java and Banten, Tbk. to obtain profit or profit from the difference in interest given to individual customers or business entities. The purpose of this study is to determine the effect of credit on cash flow at PT Regional Development Bank of West Java and Banten, Tbk. The method used in this research is quantitative with simple linear regression analysis to determine the effect of credit on cash flow, data collection techniques in this study are observation, documentation, literature study and internet browsing. The results showed that credit to cash flow had a strong and positive effect, which meant that there was a unidirectional and significant relationship. There are obstacles that occur, namely the slowdown in lending from 2018-2021 and the implementation of the NSFR. In dealing with these obstacles, efforts have been made to improve credit quality through optimizing credit repeats, adding transaction features to mobile and internet banking application DigiCash.